Upaya Meningkatkan Kemampuan Sholat pada Mata Pelajaran PAI Melalui Metode Demonstrasi Berbasis Kartu Pada Peserta Didik Kelas 3 SDN 1 Plumbon - Fathus Sodiq; Siti Fatimah (Tarbi: Jurnal Ilmiah Mahasiswa, 2023)
Learning to pray using the demonstration method with card media on prayer material hasstrategic and important value in preparing superior and moral human resources. This has beenan obstacle so far in learning using interesting, challenging and fun methods, so this is thebackground for conducting classroom action research. This research aims to increase students'ability to pray in PAI subjects through the 3rd grade demonstration method at SDN 1PLUMBON, Plumbon village. This research was conducted in two cycles. From researchconducted by the author, it can be shown that there has been an increase in prayer learningoutcomes for grade 3 students at SDN 1 PLUMBON, these learning outcomes can be knownthrough tests, observations and interviews. Validate the data using the triangulation technique.The results of the analysis show that 70% of cycle 1 has been completed. Meanwhile, in cycle2 learning, 90% of students had completed understanding the prayer material. So it can beconcluded that there has been an increase in students' understanding of prayer materialthrough the demonstration method and card media